DAMPAK PENGGUNAAN LKPD BERBASIS ETNOMATEMATIKA DENGAN KONTEKS BATIK JAMBI TERHADAP KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS PESERTA DIDIK - Melly Satriani (Departemen Matematika, 2022)
One of the objectives that should be accomplished by students in learning mathematics is understanding mathematical concepts. Truth be told, the comprehension of the ideas of class students at SMPN 10 Batang Hari is as yet in the low classification, this should be visible from the consequences of daily students evaluations where students experience issues responding to a few inquiries that contain marks of understanding mathematical concepts. The arrangements that should be possible to tackle this issues is to utilize ethnomathematics-based worksheet with regards to Jambi batik. The reason for this review was to decide and describe the development of the capacity to understand mathematical concepts of class IX SMPN 10 Batang Hari after using ethnomathematics-based worksheet in the context of Jambi batik. This research is a pre-experimental research using One Shot Case Study design. The subjects of this exploration were students of class IX.A SMPN 10 Batang Hari. This research data was collected through a final test of the capacity to understand mathematical concepts in view of the acquisition of the students average score of the each indicator and the percentage of the quantity of students in each score obtained. In view of information investigation, it tends to be presumed that the development of understanding mathematical concepts of class IX.A students of SMPN 10 Batang Hari after using ethomathematics-based worksheet in the context of Jambi batik is very good and has increased in each indicator. The average acquisition of the final test is 82,8 with a very good category. Keywords– Ethnomatematics, Jambi Batik, understand mathematical concept, worksheet, pre-experiment